Experiências e vivências de famílias homoafetivas com filhos: vozes de pais, mães e filhos - Farias, Mariana de Oliveira (2017)
Homophobia is still alive in our society and sustains itself by the heteronormativity that orders what would be considered ideal and expected in the affective-sexual relations and in the gender relation as well. The ideal affective-sexual relation considered is the heterosexual monogamous marriage with children. The Christianism and later, the Science validated a heteronormativity. According to this, there are many myths related to the homosexuality and, consequently, for the homosexual families with children, sustained critics related to the well-being of children and teenagers who live with these families. On the other hand, there are critics in relation to the homosexual people who are looking for a marriage and also desire kids in their relation; this , for some authors, would correspond to a reproduction of actual hegemonical rules. According to this, the present study search for describing and understanding the experience and living for lesbian mothers, gay fathers and their children as active authors from this research about their familiar configuration, the familiar relationship and their relations with the society. Twelve couples (seven male couples and five female couples) and their children participated into this research. They are from Ceará, São Paulo or Rio de Janeiro states. Twenty-three children and teenagers, from 5 to 18 years old, were interviewed; all of them attend to the regular school program. The method, which was used in this research, was the Grounded Theory and, as a complementary method to data dealing, the analysis of the content. The results showed that the familiar conception, according to the fathers, the mothers or the children, are related to the affective feelings and its quality into the established relation. The children showed that there are affection and happiness into their relation with the families. Therefore, the homophobia, the racial prejudice, in relation to some children, and the adoption prejudice permeate the relation between these families and the society. The schools seem not to be prepared to deal with the familiar and sexual diversity, in spite of some institutions try to receive the members of these families. Many mothers and fathers describe the importance of the visibility and representativity of homosexuality and homoaffective families with children in the broadcast midia, as well as the participation of LGBT social movement, in the associations or groups related to the LGBT issues or adoptions. The results of this study show that the members from the interviewed families, in spite of sometimes, reproduced values considered traditional and heteronormative, transform the social order from the affection valorization and also from the socio-affective feeling into the familiar relation to the detriment of biological relation and from the expectatives of antagonic gender from the partners. The present study showed itself essential against the scarcity of empiric Brazilian studies about this thematic